Relationship between external factors and behavioral intention of virtual reality implementation among vocational college students - Yao, Ling; Marlissa Omar,; Mohamad Sattar Rasul, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Virtual reality (VR) technology has garnered increasing attention for its potential to improve learning outcomes in English learning in vocational colleges. Understanding the behavioral intention to use VR is essential for successful implementation. In practice, behavioral intention is shaped by external factors through multiple aspects, including previous experience, related training, policy, perceived cost and technicality. This study explored the relationship between external factors and behavioral intention to use VR in English learning, and provided insights into how these factors impact the acceptance of innovative educational tools. A quantitative research method was conducted and 520 vocational college students in Jilin Province, China involved in this study. The data were analyzed using Smart-PLS to assess the path coefficient results of the variables. The results showed that external factors were slightly positively correlated, but not statistically significant. Consequently, the hypothesis was rejected, indicating that external factors had no significant effect on behavioral intention to implement VR technology. These findings highlight the need to explore other factors that influence the adoption of VR in educational settings.